Charlie One Five : A Marine Company's Vietnam War - Warr, Nicholas, 1945- (Book collections on Project MUSE., 2013)
"The Vietnam War combat history of the U.S. 1st Battalion, 5th Marines, known as Charlie 'One Five' (1/5); drawn from historical research, command chronologies, combat after-action reports, and first-person accounts"--Provided by publisher.